(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The higher state educational standard requires students to be specialists (bachelor) in the field of physical culture and have knowledge of socio-economic sciences: understanding the role of physical culture in human development and professional training; possessing a system of practical skills and qualifications that ensure the preservation and strengthening of health, the development and improvement of psychophysical abilities, qualities, and self-determination in physical culture; and gaining experience to achieve life and professional goals. Sports games and their teaching methodology. It can be used by students of the Faculty of Physical Education, masters and physical education teachers of secondary schools, coaches of basketball, volleyball, football and handball players of primary training groups of sports schools, organizers and instructors of physical education, and all fans of these sports.